KONSEP PERANCANGAN MODUL PEMBELAJARAN PEMBENTUKAN VIDEO TUTORIAL - Renata Kusuma; Sony Dharsono Kartika; Wegig Murwonugroho (Jurnal Seni dan Reka Rancang: Jurnal Ilmiah Magister Desain, 2023)
AbstractDesigning Concept of A Learning Module to Create Tutorial Videos This research is formed in order to find a new concept as alternative teaching materials because the existing learning modules for creating video tutorials are less attractive and outdated for today’s learners. Most of them only discuss technical matters like explaining how to use recording tools or video editing applications,so the resulting video tutorials are boring. Meanwhile, nowadays students need more guidance on the idea of producing creative video tutorials. The purpose of this study is to define the new concept of making modules that support creativity in creating video tutorials that are able to lock the attention of viewers. The research uses an artistic research approach. Ethical data and emic data are used in the study. Ethical data were collected from literature studies, and emic data were collected from analysis of study documentation and interviews with several students as resource persons. The expected result of this research is to find a new concept that is more suitable for today’s learners, where the characteristics of the learners are digital natives. From the research, it was found that the concept of meaningful learning that supports cognitive processes and e-learning, is more suitable for today’s learners who need to study in an independent manner because they are digital natives. AbstrakKonsep Perancangan Modul Pembelajaran Pembentukan Video Tutorial disusun sebagai penelitian dalam mencari alternatif bahan ajar yang baru karena modul pembelajaran pembentukan video tutorial yang sudah ada terlihat kaku dan sudah ketinggalan zaman bagi pembelajar masa kini. Kebanyakan hanya membahas hal-hal teknis yang menjelaskan mengenai penggunaan alat atau cara menggunakan aplikasi mengedit, sehingga video tutorial yang dihasilkan membosankan. Pembelajar sekarang ini lebih membutuhkan modul tuntunan dalam menghasilkan video tutorial yang kreatif. Tujuan penelitian ini adalah memaparkan terciptanya konsep modul pembelajaran yang merangsang kreativitas dalam penciptaan karya. Video tutorial yang diciptakan diharapkan mampu mengunci perhatian viewers-nya. Penelitian menggunakan pendekatan kualitatif dengan metode penelitian artistik. Data etik dan data emik digunakan dalam penelitian. Data etik dikumpulkan dari studi pustaka, dan data emik dikumpulkan dari analisa studi dokumentasi serta wawancara kepada sejumlah mahasiswa sebagai narasumber. Dari penelitian ditemukan konsep belajar bermakna yang mendukung proses kognitif dan e-learning, lebih sesuai untuk kebutuhan belajar mandiri dimana karakteristik pembelajar masa kini adalah digital native.